Arabidopsis glucosinolate storage cells transform into phloem fibres at late stages of development. (12th April 2019) - Hunziker, Pascal; Halkier, Barbara Ann; Schulz, Alexander
Abstract : Glucosinolate-storing S-cells are symplasmically coupled to glucosinolate-synthesizing cells and lignify during the final stages of differentiation, as revealed by a combination of improved TEM fixation and bioimaging. Abstract: The phloem cap of Arabidopsis thaliana accumulates glucosinolates that yield toxic catabolites upon damage-induced hydrolysis. These defence compounds are stored in high concentrations in millimetre long S-cells. At early stages of development, S-cells initiate a process indicative of programmed cell death. How these cells are maintained in a highly turgescent state following this process is currently unknown. Here, we show that S-cells undergo substantial morphological changes during early differentiation. Vacuolar collapse and rapid clearance of the cytoplasm did not occur until senescence. Instead, smooth endoplasmic reticulum, Golgi bodies, vacuoles, and undifferentiated plastids were observed. Lack of chloroplasts indicates that S-cells depend on metabolite supply from neighbouring cells. Interestingly, TEM revealed numerous plasmodesmata between S-cells and neighbouring cells. Photoactivation of a symplasmic tracer showed coupling with neighbouring cells that are involved in glucosinolate synthesis. Hence, symplasmic transport might contribute to glucosinolate storage in S-cells. To investigate the fate of S-cells, we traced them in flower stalks from the earliest detectable stages to senescence. At late stages, S-cells were shown to deposit thick secondary cell walls and transform into phloem fibres. Thus, phloem fibres in the herbaceous plant Arabidopsis pass a pronounced phase of chemical defence during early stages of development.